Melt extruded versus extrusion compression molded glass-polypropylene long fiber thermoplastic composites. (May 2021) - Alwekar, Shailesh; Yeole, Pritesh; Kumar, Vipin; Hassen, Ahmed Arabi; Kunc, Vlastimil; Vaidya, Uday K.
Abstract: Long fiber thermoplastic (LFT) composites are processed either with extrusion compression or fiber injection processes. The properties of LFT materials are highly influenced by processing techniques, which lead to different porosity contents, fiber length distributions, and fiber orientation distributions. It is important to understand the various LFT processing techniques and their effects on mechanical, thermal, and microscopic properties. This work considered LFT sheets processed via extrusion, which offers highly aligned fibers (referred to as "Tecnogor composites"), and LFT composites produced via extrusion compression molding (ECM), which offers a random distribution of fibers. Tecnogor composites exhibited higher flexural strength (35–65%), flexural modulus (132–172%), tensile strength (39–52%), tensile modulus (67–75%), and Izod impact resistance (195–220%) than the random LFT composites. This response was attributed to the aligned fibers in Tecnogor composites. Mathematical models including Halpin-Tsai and Lavengood-Goettler were used to predict and compare the Young's modulus of Tecnogor and ECM composites, respectively.